2007
DOI: 10.1108/00070700710746803
|View full text |Cite
|
Sign up to set email alerts
|

Purchasing organic food in US food systems

Abstract: Consumers' preference for organic foods in the context of food aspects considered important in a consumption decision and socioeconomic variables has been examined in this study. The results indicate that food aspects related to naturalness, vegetarian-vegan and production location were critical enhancing regularity of organic food purchases.While the familiarity food aspect was viewed as a 'no' issue as far as organic food purchases are concerned. Results further indicate that females and young people buy org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
110
4
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(130 citation statements)
references
References 10 publications
14
110
4
2
Order By: Relevance
“…The dynamics of the Czech organic food market imitate the growing trend of the markets in the West European countries and the USA (Onyango et al 2007); the majority of sales represent cereals (crop production) and beef (livestock) (Václavík 2008). Despite the fact that organic food still constitutes a relatively small portion of the food market (Raynolds 2000), thanks to the growing interest of customers, the previously small niche of the market changes over time into a significant segment and the marketing principles are increasingly taken into consideration.…”
mentioning
confidence: 99%
“…The dynamics of the Czech organic food market imitate the growing trend of the markets in the West European countries and the USA (Onyango et al 2007); the majority of sales represent cereals (crop production) and beef (livestock) (Václavík 2008). Despite the fact that organic food still constitutes a relatively small portion of the food market (Raynolds 2000), thanks to the growing interest of customers, the previously small niche of the market changes over time into a significant segment and the marketing principles are increasingly taken into consideration.…”
mentioning
confidence: 99%
“…female sex, infants in the household and a higher age, were positively associated with organic food buying behaviour [5] [61]. However, other studies found that mainly younger people buy organic food [62]. Hence, effects of sex, age, education and children in the household can be expected, though the direction is an open question for age.…”
Section: Socio-demographic Characteristicsmentioning
confidence: 64%
“…However, it has been shown that political views may be associated with food purchasing practices, 65 so it is surprising that neither construct was associated with politics. Future studies are required to determine the reliability of this result before any conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…59 Additionally, vegetarian/vegan self-identity has been associated with purchasing of organic foods. 65 Based on evidence connecting self-identity shifts and behavior change, creating an identity shift based on moral foundations may promote healthy eating in a way that focuses on ethics as opposed to improving health knowledge.…”
Section: Conclusion and Applicationsmentioning
confidence: 99%